1990
DOI: 10.1037/0735-7044.104.4.597
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of conditioned associations in Hermissenda: Additive effects of contiguity and the forward interstimulus interval.

Abstract: Conditioned suppression of photokinesis by the marine mollusc Hermissenda was examined in 3 experiments. In each experiment, groups of animals received light (the conditioned stimulus, CS) that was paired with high-speed orbital rotation (the unconditioned stimulus, UCS), light and rotation explicitly unpaired, or no exposure to these stimuli. Twenty-four hours after training, all animals were tested for suppression of photokinesis in the presence of the light. To establish the effectiveness of our conditionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…used longduration (30 sec) turntable-induced rotation to achieve vestibular stimulation. In contrast, we have successfully used brief (2-3 sec) orbital rotation as a US in numerous studies (Matzel & Rogers, 1993;Matzel, Schreurs, Lederhendler, & Alkon, 1990;Rogers, Fass, & Matzel, 1992;Rogers et a\., 1994). Although both techniques result in the stimulation ofhair cells within the vestibular organ, differences arise as to the pattern of stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…used longduration (30 sec) turntable-induced rotation to achieve vestibular stimulation. In contrast, we have successfully used brief (2-3 sec) orbital rotation as a US in numerous studies (Matzel & Rogers, 1993;Matzel, Schreurs, Lederhendler, & Alkon, 1990;Rogers, Fass, & Matzel, 1992;Rogers et a\., 1994). Although both techniques result in the stimulation ofhair cells within the vestibular organ, differences arise as to the pattern of stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneous measurement of both locomotion and foot contraction revealed that there is a rapid decrease in locomotion and a gradual increase in foot contraction as a function of training (Matzel et al, 1990a). Finally, foot contraction was also shown to be a function of the number of CS-US pairings and of the interval between the CS and US (Matzel et al, 1990b).…”
Section: Hermissendamentioning
confidence: 95%
“…This expectation has been verified in animal experiments using 30 second [SI and shorter [6] stimuli. The model also exhibits effective learning only when the CS and the US coterminate.…”
Section: Comparison Of Model and Animal Learningsupporting
confidence: 52%
“…For effective learning to occur, the time interval between the onsets of the light and rotation must occur within a narrow range. A behavioral experiment that examined the role of the IS1 in associative learning was performed by Matzel et al [6]. In this experiment, the animals were presented with 150 repetitions of light (CS) paired with rotation (US).…”
Section: Comparison Of Model and Animal Learningmentioning
confidence: 99%